Control in Large Organizations - Arrow, Kenneth J. (Management Science, 1964)
The problem of control is defined as that of choosing operating rules for members of an organization and enforcement rules for the operating rules so to maximize the organization's objective function. The control problem is sketched for three characteristic types of large organizations: large corporations, governments in their budgetary aspects, and economic systems as a whole. The essential roles of uncertainty and of differential amounts of information in different parts of an organization in the problem of control are brought out. The merits and drawbacks of the price system as a control mechanism are discussed in light of the preceding discussion, with especial reference to the effects of uncertainty.